Isu Terkini Euthanasia Antara Hak Hidup dan Hak Menentukan Pilihan: Systematic Literature Review: Current Issues in Euthanasia Between the Right to Life and the Right to Choose: A Systematic Literature Review - Reza, Muhammad Alfi; Diennillah, Fathannia Rizky (Journal of Aafiyah Health Research (JAHR), 2023)
Abstract Background: Euthanasia up to now, there are still no regulations or regulations that are legally implemented and apply in Indonesia, including criminal responsibility for the perpetrator or family who wants euthanasia. Currently, euthanasia is discussed more often and is equated with the action of a doctor or health worker who carries out the act or act of injecting a patient to death at the request of the patient himself or at the request of the victim's family. There are various opinions about the pros and cons of euthanasia, including being faced with two difficult choices, namely the right to life and the right to make choices. Aim: This research aims to explore the act of euthanasia, both active and passive, along with ethical and moral dilemmas Method: The method used in this writing is a literature review which is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practitioners. Results: The research results show that euthanasia is an ethical and moral dilemma in the code of ethics of health professionals because they are faced with a difficult choice between complying or not complying with requests from the patient/family directly and indirectly. Passive euthanasia is still ethically acceptable with several considerations, but active euthanasia is opposed to being carried out on ethical, moral and legal grounds. The right to life must not be revoked arbitrarily or "arbitrarily deprived" which is implemented by limiting the scope of this right, and therefore it is the state's duty to ensure the right to life. Countries that allow euthanasia must provide effective safety procedures so that it is not used as an abuse. Conclusion: Euthanasia is an ethical and moral dilemma in the code of ethics for health professionals because they are faced with a difficult choice between complying or not complying with requests from the patient/family directly and indirectly. Passive euthanasia is still ethically acceptable with several considerations, but active euthanasia is opposed on ethical, moral and legal grounds.